PENGARUH MOTIVASI KERJA DAN PENGENDALIAN DIRI TERHADAP PERILAKU KERJA GURU PNS SMP NEGERI SE-KECAMATAN MINAS KABUPATEN SIAK - RIKO ALFIAN BIN IDRUS; ISJONI ISJONI; AZHAR AZHAR (Universitas Riau, 2017)
The aim of this research is to know about the influence between variables (1)work motivation toward teacher work behavior in junior high schools of Minas sub district SiakRegency, (2) self control toward teacher work behaviour in junior high schools of Minas subdistrict Siak Regency, (3) work motivation and self control together toward teacher work behaviourin junior high schools of Minas sub district Siak Regency. This research carried out by spreadingthe instruments for 99 administrator in junior high schools of Minas sub district Siak Regency byusing proportionate random sampling technique. The instrument used to collect the data of allvariables using the questionnaire. Validity was tested using Pearson product moment formula.Instrument reliability coefficient was calculated using Cronbach alpha formula. The resultsshowed a positive relationship between: (1) There is a positive influence between work motivationtoward teacher work behaviour in junior high schools of Minas sub district Siak Regency witha correlation coefficient rx1. y = 0,344 and the regression equation 107,229 + 0,168 X1. (2)There is a positive influence between self control toward teacher work behaviour in junior highschools of Minas sub district Siak Regency with correlation coefficients rx2. y = 0,656 and theregression v = 81,39 + 0,366 X2. (3) There is a positive influence between work motivation andself-control toward teacher work behaviour in junior high schools of Minas sub district SiakRegency with Rx1 x2.y multiple correlation coefficient = 0,701 and the regression equation v =70,06 + 0,122X1 + 0,345 X2. The results of this study are expected to be useful for the improvementand enhancement of teae herwork behaviour in junior high schools of Minas sub district SiakRegency by increasing work motivation and self control.